Risks of metabolic syndrome in the ADVANCE and NAMSAL trials - Tovar Sanchez, Tamara; Mpoudi-Etame, Mireille; Kouanfack, Charles; Delaporte, Eric; Calmy, Alexandra; Venter, Francois; Sokhela, Simiso; Bosch, Bronwyn; Akpomiemie, Godspower; Tembo, Angela; Pepperrell, Toby; Simmons, Bryony; et al. (Frontiers in Reproductive Health, 2023)
Introduction The ADVANCE and NAMSAL trials evaluating antiretroviral drugs have both reported substantial levels of clinical obesity in participants. As one of the main risk factors for metabolic syndrome, growing rates of obesity may drive metabolic syndrome development. This study aims to evaluate the risk of metabolic syndrome in the ADVANCE and NAMSAL trials. Methods The number of participants with metabolic syndrome was calculated at baseline and week 192 as central obesity and any of the following two factors: raised triglycerides, reduced HDL-cholesterol, raised blood pressure and raised fasting glucose. Differences between the treatment arms were calculated using the χ2 test. Results Across all visits to week 192, treatment-emergent metabolic syndrome was 15% (TAF/FTC + DTG), 10% (TDF/FTC + DTG) and 7% (TDF/FTC/EFV) in ADVANCE. The results were significantly higher in the TAF/FTC + DTG arm compared to the TDF/FTC/EFV arm (p < 0.001), and the TDF/FTC + DTG vs. the TDF/FTC/EFV arms (p < 0.05) in all patients, and in females. In NAMSAL, the incidence of treatment-emergent metabolic syndrome at any time point was 14% (TDF/3TC + DTG) and 5% (TDF/3TC + EFV) (p < 0.001). This incidence was significantly greater in the TDF/3TC/DTG arm compared to the TDF/3TC/EFV arm in all patients (p < 0.001), and in males (p < 0.001) Conclusion In this analysis, we highlight treatment-emergent metabolic syndrome associated with dolutegravir, likely driven by obesity. Clinicians initiating or monitoring patients on INSTI-based ART must counsel for lifestyle optimisation to prevent these effects.